2010
DOI: 10.3233/jad-2010-100948
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Induces Caspase-Dependent Loss of PSD-95 and Synaptophysin Through NMDA Receptors

Abstract: Soluble oligomeric amyloid-β (Aβ) is thought to induce synaptic dysfunction during early stages of Alzheimer's disease (AD). In this report, we show that soluble Aβ downregulates the levels of two synaptic proteins, PSD-95 and synaptophysin, and that this effect can be blocked by MK-801 (NMDAR antagonist) and ifenprodil (NR2B antagonist). Low (1 μM) and high (10 μM) doses of NMDA, respectively, prevented and potentiated the actions of Aβ. Blockade of NR2A or synaptic NMDAR eliminated the protective effect of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 0 publications
8
63
1
Order By: Relevance
“…The expression of NR2A and NR2B is lower in susceptible regions of the AD brain compared to normal controls (Yashiro and Philpot, 2008). A␤ promotes NMDA receptor endocytosis in cultured neurons Roselli et al, 2005;Snyder et al, 2005) and down regulates synaptic proteins by disrupting the function of the NMDA receptor (Liu et al, 2010). Increasing the protein phosphatase 2B (PP2B) activity induced by A␤ can dephosphorylate the tyrosine phosphatase STEP and then promote NR2B trafficking away from the surface .…”
Section: Discussionmentioning
confidence: 98%
“…The expression of NR2A and NR2B is lower in susceptible regions of the AD brain compared to normal controls (Yashiro and Philpot, 2008). A␤ promotes NMDA receptor endocytosis in cultured neurons Roselli et al, 2005;Snyder et al, 2005) and down regulates synaptic proteins by disrupting the function of the NMDA receptor (Liu et al, 2010). Increasing the protein phosphatase 2B (PP2B) activity induced by A␤ can dephosphorylate the tyrosine phosphatase STEP and then promote NR2B trafficking away from the surface .…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that enhancement of GluN2A activity and/or the reduction of GluN2B activity may be used in order to halt the early Aβ-mediated synaptic dysfunction (Liu et al, 2010). Taking into account the importance of ERK for cell survival (described previously in this review), a negative regulation by extrasynaptic NMDARs, mainly composed of GluN2B subunits (Tovar and Westbrook, 1999;Petralia, 2012), may be one of the early signaling events determining brain injury in AD (Ivanov et al, 2006).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In both AD patients and animal models of this disease, the greastest synapse loss is near senile plaques, indicating a link between Aβ pathology and synaptotoxicity in vivo [7,8] . Furthermore, AβOs have been www.chinaphar.com Zhang LL et al Acta Pharmacologica Sinica npg shown to downregulate the levels of two synaptic proteins, postsynaptic density-95 (PSD-95) and synaptophysin [9] . PSD-95 is an abundant postsynaptic scaffolding protein that plays a critical role in synapse maturation and synaptic plasticity [10] .…”
Section: Introductionmentioning
confidence: 99%